Evaluating the implementation of a multicomponent asthma education program for Head Start staff. (1st February 2019) - Ruvalcaba, Elizabeth; Chung, Shang-En; Rand, Cynthia; Riekert, Kristin A.; Eakin, Michelle
ABSTRACT: Objective : Asthma disproportionately affects minority groups, low income populations, and young children under 5. Head Start (HS) programs predominantly serve this high-risk population, yet staff are not trained on asthma management. The objective of this study was to assess a 5-year, multicomponent HS staff asthma education program in Baltimore City HS programs. Methods : All HS programs were offered annual staff asthma education by a medical research team that included didactic lectures and hands-on training. Attendees received continuing education credits. HS staff were anonymously surveyed on asthma knowledge and skills and asthma medication management practices in Year 1 (preimplementation) and Year 5. Results : There was an estimated response rate of 94% for Year 1 and 82% for Year 5. Compared to staff in Year 1, Year 5 staff were significantly more likely to report they had very good knowledge and skills related to asthma [odds ratio (OR) 1.63; p < 0.05] and were engaged in asthma care activities (OR 2.02; p < 0.05). Self-reported presence of asthma action plans for all children with asthma was 82% at Year 1 and increased to 89% in Year 5 ( p = 0.064). Conclusions : Year 5 HS staff reported higher self-assessed knowledge and skills, self-reports of asthma medication management practices, and self-reports of asthma activities compared to Year 1 staff. HS serves high-risk children with asthma, and a multicomponent program can adequately prepare staff to manage asthma in the child care setting. Our results indicate the feasibility of providing efficacious health skill education into child care provider training to reduce asthma knowledge gaps.